Foundations of the Formation of Translation Theory in Uzbekistan - Azodovna, Bakhadirova Dildora; Jaxangirovna, Khusnutdinova Aziza (PT. Antis International Publisher, 2024)
The study of translated works is also important for the study of the history of translation. Because the principles, methods and techniques of translation, which are a unique field of creativity, have improved over time, traditions have been formed and developed, mutual benefit, influence and literary-artistic ties have increased. Therefore, it is important to study each period of the history of translation, each translation separately.